Metformin blocks myeloid-derived suppressor cell accumulation through AMPK-DACH1-CXCL1 axis - Qin, Guohui; Umansky, Viktor (OncoImmunology, 2018)
Purpose: Tumor development has been closely linked to tumor microenvironment, particularly in terms of myeloid-derived suppressive cells (MDSCs), a heterogeneous population of immature myeloid cells that protect tumors from elimination by immune cells. Approaches aimed at blocking MDSC accumulation could improve cancer clinical outcome. Experimental Design: We investigated that metformin suppressed MDSC migration to inhibit cancer progression. Primary tumor tissues were incubated with metformin, and proinflammatory chemokine production was measured. To study MDSC chemotaxis in vivo, BALB/C nude mice were injected subcutaneously with TE7 cells and treated with metformin. Migration of adoptively transferred MDSCs was analyzed using flow cytometry and immunohistochemistry. Results: The frequency of tumor-infiltrated polymorphonuclear (PMN)-MDSCs was increased compared to their circulating counterparts. There was a significant correlation between PMN-MDSCs accumulation in tumors and ESCC prognosis. Moreover, PMN-MDSCs displayed immunosuppressive activity in vitro. Treatment with metformin reduced MDSC migration in patients. Metformin inhibited CXCL1 secretion in ESCC cells and tumor xenografts by enhancing AMPK phosphorylation and inducing DACH1 expression, leading to NF-κB inhibition and reducing MDSC migration. Knockdown of AMPK and DACH1 expression blocked the effect of metformin on MDSC chemotaxis. Conclusions: A novel anti-tumor effect of metformin, which is mediated by reducing PMN-MDSC accumulation in the tumor microenvironment via AMPK/DACH1/CXCL1 axis.